Representación pictórica surrealista - onírica de la figura humana masculina, con una poética personal y técnicas contemporáneas - Cruz Tenemaza, Elvia Rosario (2022)
The artistic work entitled: SURREALIST-ONIRIC PICTORIAL REPRESENTATION OF THE MALE HUMAN FIGURE, WITH A PERSONAL POETIC AND CONTEMPORARY TECHNIQUES. It proposes the analysis of the representation of the human figure in dream painting, through the study of its morphology, to support the representation of pictorial production, based on the personal poetics of dreams, fantasy and personal experience. The research is artistic, it is part of the type of qualitative research, bibliographic data was recorded in the theoretical work. The development of the themes influenced the elaboration of the practical work. Considering the following investigations; bibliographic documentary research and experimental research; carrying out a process of selection, systematization and analysis of the information, allowing the writing of the contents of the chapters and the elaboration of the pictorial work, through the observation of the human figure, a photographic study, preparatory drawings and compositional sketches, as part of the process of representation and experimentation of materials, such as oil on mdf and the combination of the photomontage technique, which allows the manipulation of the work through digital programs such as inffinity photo and procreate, finally the entire theoretical-practical process facilitates the diffusion and exhibition of the final works.